2020
DOI: 10.1177/0309524x20941180
|View full text |Cite
|
Sign up to set email alerts
|

Trend-based time series data clustering for wind speed forecasting

Abstract: Wind forecasting is a time series problem, can aide in estimating the annual energy production of potential wind farms. Seasonality and trend are the two significant components that characterize the wind time series data. Variability in trend and seasonal component affects the performance of most of the forecasting methods. Therefore, to simplify the wind forecasting technique, generally, nonlinear seasonal and trend components are eliminated from wind time series data. Accuracy depends on the application func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Forecasting time series has several applications in different domains, many of them are instrumented using deep learning models (Brahma and Wadhvani, 2020a), (Kushwah et al, 2021), (Tran et al, 2019), (Gharehbaghi and Linden, 2018). Wind speed forecasting models for 15 years are reviewed by Sheela and Deepa (2013), concluding that the models of neural networks outperform non-neural network models.…”
Section: Introductionmentioning
confidence: 99%
“…Forecasting time series has several applications in different domains, many of them are instrumented using deep learning models (Brahma and Wadhvani, 2020a), (Kushwah et al, 2021), (Tran et al, 2019), (Gharehbaghi and Linden, 2018). Wind speed forecasting models for 15 years are reviewed by Sheela and Deepa (2013), concluding that the models of neural networks outperform non-neural network models.…”
Section: Introductionmentioning
confidence: 99%
“…The grouping focuses on the patterns and seasonality of time series data values for each instance. Based on the trend and seasonality to recognize the same kind of structure of the instances for the grouping (Kushwah et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The results indicate that the hybrid version had better accuracy than the unbiased versions of ARIMA and ANN. Kushwah et al (2020) suggested a hybrid model consisting of statistical models and trend-based clustering. Compared to statistical models used alone, the hybrid model performs better.…”
Section: Introductionmentioning
confidence: 99%